2008
DOI: 10.1111/j.1349-7006.2008.00841.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of the WWOX gene, encompassing fragile region FRA16D, in suppression of pancreatic carcinoma cells

Abstract: The WW-domain-containing oxidoreductase (WWOX) gene spans the common chromosomal fragile site FRA16D (16q23.2) and is believed to be a tumor suppressor in various human malignancies. We have previously shown frequent down-modulation of Wwox expression in pancreatic carcinoma (PC); however, biological function of Wwox in pancreatic duct carcinogenesis remains unknown. In PANC-1 (Wwox-negative) PC-derived cells, restoration of recombinant WWOX gene expression with adenoviral gene delivery (Ad-WWOX) effectively i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
40
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 37 publications
6
40
2
Order By: Relevance
“…In this study, we found frequent reduction of WWOX expression in IPMC, which was almost equivalent to the frequency of WWOX reduction in IDC (Nakayama et al, 2008). In turn, WWOX expression was relatively retained in most IPMAs, suggesting that reduced WWOX expression does not contribute to development of IPMA.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…In this study, we found frequent reduction of WWOX expression in IPMC, which was almost equivalent to the frequency of WWOX reduction in IDC (Nakayama et al, 2008). In turn, WWOX expression was relatively retained in most IPMAs, suggesting that reduced WWOX expression does not contribute to development of IPMA.…”
Section: Discussionmentioning
confidence: 58%
“…In pancreatic carcinoma cells and IDC tissue samples, a close correlation has been documented between hypermethylation of the WWOX regulatory region and low WWOX expression levels rather than LOH at the WWOX locus (Nakayama et al, 2008). In BxPC-3 (low WWOX expression) cells, frequent hypermethylation at the WWOX regulatory sites was detected by bisulphite sequencing (Figure 2A).…”
Section: Hypermethylation Of the Wwox Regulatory Site In Ipmnmentioning
confidence: 96%
See 3 more Smart Citations